Binding for life: corticosteroid binding globulin from vertebrate physiology to human diseases - Le Rouzic, Philippe; Rousseau, Karine (Frontiers in Endocrinology, 2025)
The hypothalamic-pituitary-adrenal/interrenal axis (HPA/HPI) is the neuroendocrine axis which allows vertebrates to cope with changing environments via adaptative stress responses. Glucocorticoids (GC) are the main effectors of this corticotropic axis, and their plasma levels (free form) are elevated under stress conditions. In contrast, in normal conditions, in order to prevent their deleterious impact on tissues, GC are found bound to a binding protein, the corticosteroid binding globulin (CBG). This protein, also called transcortin, was discovered in the 1950s, and later shown to be part of the SERPIN family (SERPINA6). Most vertebrates present high levels of bound GC, but some exceptions exist such as lamprey, flying squirrel or New World monkey. In birds, CBG is reported to be the substitute for sex hormone-binding globulin (SHBG) as well since they lack shbg gene. In amphibians, CBG binds GC and sex steroids with equivalty -50ently high affinity. In teleosts, up to now, no CBG has been characterized. Mainly synthetized by the liver, the CBG is released in the blood where it serves as a GC transporter and address them to the sites of inflammation and infection. Evidences accumulate to propose CBG as also a GC reservoir. Other functions, under-characterized for the moment, have also been reported for the CBG: extrahepatic CBG could prevent the GC to bind to their receptor(s) intracellularly, and circulating CBG-GC complex could bind to a receptor which allows its internalization in target cells by endocytosis. The concentrations of the plasma CBG show natural physiological variations during specific life-history stages such as during pregnancy and hibernation in mammals, or breeding season in birds. Vertebrates may also present fluctuating CBG when experiencing extreme conditions leading to food deprivation for example. CBG knockout in mice and mutations in human stressed out the functional importance of CBG. In human, a CBG deficit is associated with a number of patho-physiologies including endocrine diseases (hypo- or hyper-thyroidism, obesity) and pro-inflammatory pathologies (sepsis, burning). Our review begins by a description of CBG discovery, characterization and measurement in vertebrates. A focus on the variations of CBG concentrations in various physiological conditions or under non-natural situations in vertebrates follows. The current knowledge on the different functions reported for CBG is then unfold. Our review ends with CBG pathological alterations observed in human to evidence how this protein could have therapeutic uses.